Time for a Committee C for the WHO? COVID-19 and a more inclusive participation and accountable WHO - Tsung-Ling Lee (Inishmore Laser Scientific Publishing Ltd, 2020)
Much of World Health Organization's (WHO) creditability and legitimacy as a global public health agency now hinges upon its leadership to coordinate international health work, as well as effectiveness of the International Health Regulations (IHR). With the IHR lacking robust accountability mechanisms for compliance and oversight, the article proposes an establishment of a Committee C of the World Health Assembly-an idea first put forward by Gaudenz Silberschmidt, Don Matheson, Ilona Kickbusch-not as a pancreas to the chronic shortfalls of the WHO, but as an additional governance mechanism to improve accountability and transparency at the organization. Democratizing global governance of health would rebuild trust and engender global solidarity, the foundations for a resilient global health system.